The five-year itch: motivational factors that influence the career decisions of early career teachers in England - Procter-Legg, T; Snell, R; Klassen, R (Wiley, 2025)
Teacher retention in England continues to be in a state of decline, with early career teachers (ECTs) most at risk of leaving the profession. High attrition rates create an unstable and unsustainable workforce, which negatively affects the educational development of young people. The purpose of this paper was to explore the career-related push and pull factors for ECTs in England. The paper also explores the way in which ECTs' experiences shape career decision-making, and the extent to which their motivational needs are being met. Previous studies have considered workplace retention; however, little is known about the motivational needs and perspectives of ECTs. This paper explores the experiences of 20 ECTs in state-funded primary, secondary and special schools in England. All participants had less than 5 years' teaching experience and were selected through purposive sampling. Participants took part in semi-structured online interviews with data analysed using reflexive thematic analysis. Five themes were constructed from the data: complexity, belonging, emotional impact, professional identity and relentlessness. Findings show that these themes are interrelated and combine to create a clear ‘tipping point’ where ECTs begin to find the job unmanageable. From a motivation perspective, we found that autonomous motivation reduces quitting intentions and that the need for relatedness and positive professional identities is particularly important for retaining teachers in the first 5 years of their careers.